Assessing the relationship between digital technology use and physical health, fitness, and exercise levels among Chinese youth: The moderating effect of parental monitoring - Ziyi Hao; Jiajia Cui (PLoS ONE, 2025)
The study investigates how digital media use, parental supervision, and attitudes towards physical activity influence young Chinese individuals’ physical health and exercise levels. Concerns over the health impacts of increasing digital technology use among teenagers have spurred extensive research. However, the specific roles of parental supervision and personal attitudes towards physical activity in mitigating or exacerbating these effects remain unclear. The study sample comprises 827 Chinese youth from diverse geographical locations. Regression analyses highlight significant predictors of physical health and exercise levels, including digital technology use (β = 0.35, p < 0.001), social media use (β = 0.22, p = 0.003), online gaming (β = 0.19, p = 0.011), educational technology use (β = 0.29, p = 0.003), parental monitoring (β = 0.47, p < 0.001), and attitudes towards physical activity (β = 0.50, p < 0.001). Additionally, the result illustrates that attitudes towards physical activity moderate the relationship between digital technology usage and physical health and exercise levels (Indirect Effect = 0.12, p = 0.003). The moderation analysis shows that digital technology use, social media use, online gaming, and educational technology use exhibit significant interactions with parental monitoring, indicating that parental supervision can mitigate the health risks associated with digital device usage.These findings underscore the crucial role of parental involvement in mitigating the health risks associated with adolescent technology use.